2008
DOI: 10.1089/jpm.2007.0268
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Implementation of an Order Protocol for End-of-Life Symptom Management

Abstract: Objectives: Designing comfort care plans to treat symptoms at the end-of-life in the hospital is challenging. We evaluated the implementation of an inpatient end-of-life symptom management order (ESMO) protocol that guides the use of opiate medications and other modalities to provide palliation.Methods: Physicians and nurses caring for patients using the ESMO protocol were surveyed about care provided and their experiences.Results: Over 342 days, 127 patients (2.6 per week) were treated using the ESMO protocol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…26,27 This guideline was adopted as the national end-of-life protocol by the Dutch Intensive Care Society in 2008. Walling et al 28 showed in that same year that a protocol for end-of-life care symptom management is indeed feasible and useful.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 This guideline was adopted as the national end-of-life protocol by the Dutch Intensive Care Society in 2008. Walling et al 28 showed in that same year that a protocol for end-of-life care symptom management is indeed feasible and useful.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Both the public and health care professionals often mistakenly believe opioid use will hasten death, when in fact appropriately dosed opioids can significantly improve pain and extend time until death. 4 According to the World Health Organization, properly dosed and titrated opioids are the medication of choice for pain management at the EOL. 5 A recent article shows that morphine is the most common opioid used at EOL.…”
Section: Introductionmentioning
confidence: 99%
“…Evaluation of the implementation of the ESMO protocol by interviewing physicians and nurses suggested that comfort measures were instituted late one quarter of the time and most patients had a life expectancy of less than 1 day. 3 When cure is no longer possible and patients are anticipated to be close to death, the best plan of care often focuses on comfort. Unfortunately, there are many barriers to the transition from curative to comfort care.…”
mentioning
confidence: 99%
“…In the interview study that led to the current chart-based analysis, 3 physicians often reported that the ESMO protocol was instituted too late and their explanation for that nearly always was that ''the patient (or family) was not ready.'' Why weren't these patients and families ready?…”
mentioning
confidence: 99%
See 1 more Smart Citation